ANALISIS STABILITAS LERENG MENGGUNAKAN APLIKASI PLAXIS 8.2 DENGAN PERKUATAN DINDING PENAHAN TANAH - Mohammad Edo Kusuma Adji; Putera Agung Maha Agung (Construction and Material Journal, 2021)
The high embankment is one of the most common problems in toll road construction projects. Embankment aims to equalize the ground elevation. Higher the embankment, the greater the load will be received by the subgrade. So, it is necessary to analyze the stability of the embankment to determine condition of stability and some important safety factor (SF) values. Slope stability planning was carried out using reinforced retaining wall with a height of 9,5 m and a width of 5,7 m. Soil foundation type was cohesive soil (clay) and the embankment soil type used non-cohesive soil (sandy). Several SF values are obtained by using Plaxis 8.2, such as: the safety factor (SF) of slope stability without and with reinforcements are 1,23 and 1,59, respectively; SF of shear stability is 2,24; SF of overturning stability of 2,1; and SF of bearing capacity is 3,36. Keywords: Plaxis 8.2, Retaining Wall Stability, Slope Stability.